Emerging Cellular Functions of Cytoplasmic PML - Jin, Guoxiang; Wang, YIng-Jan; Lin, Hui-Kuan (Frontiers in Oncology, 2013)
The tumor suppressor promyelocytic leukaemia protein (PML) is located primarily in the nucleus, where it is the scaffold component of the PML nuclear bodies (PML-NBs). PML-NBs regulate multiple cellular functions, such as apoptosis, senescence, DNA damage response and resistance to viral infection. Despite its nuclear localization, a small portion of PML has been identified in the cytoplasm. The cytoplasmic PML (cPML) could be originally derived from the retention of exported nuclear PML (nPML). In addition, bona fide cPML isoforms devoid of nuclear localization signal (NLS) have also been identified. Recently, emerging evidence showed that cPML performs its specific cellular functions in tumorigenesis, glycolysis, antiviral responses, laminopothies and cell cycle regulation. In this review, we will summarize the emerging roles of cPML in cellular functions.